HABITATION OF STAD TYPE COOPERATIVE LEARNING MODEL THROUGH PJBL APPROACH TOWARDS THE QUALITY OF MATHEMATICS LEARNING IN MUHAMMADYAH 1 SURAKARTA SCHOOL GRADE IV - Deska Sofiana Wahyu; Harun Joko Prayitno (Universitas Negeri Makassar, 2026)
This study aims to analyze the improvement in the quality of mathematics learning through the practice of cooperative learning model type Student Teams Achievement Division (STAD) combined with the Project-Based Learning (PJBL) approach in fourth-grade class at SD Muhammadiyah 1 Surakarta. The research uses a descriptive qualitative approach with 23 fourth-grade students as the subject. Data collection is done through observation, interviews, and documentation to gain a deep understanding of the learning process. The implementation of learning is carried out through a project on making